Simulation of drop-off recycling method for recyclable waste in Malaysia - H.M. Yusuf; Norhafiza Hamzah; Zaturrawiah Ali Omar (Faculty of Science and Natural Resources, 2020)
The drop-off center is one of the efficient waste collection methods for recycling and has been implemented in several developed countries. This study was conducted on three selected states in Malaysia, namely the states of Pahang, Selangor and Johor. From the construction of the model, the amount of waste recycled per year, the cost of the drop-off center per state and the profit from marketing recyclable waste materials can be obtained. With the construction of drop- off centers for each state, the waste collection process becomes more efficient and indirectly the amount of waste that has the potential to be recycled can be optimally recycled. In addition, production costs to open new landfills can be reduced.